Impact of market-based home fortification with micronutrient powder on childhood anemia in Bangladesh: a modified stepped wedge design - Sarma, Haribondhu; Rahman, Mahfuzur; Tariqujjaman, Md.; Islam, Mohammad Ashraful; Mbuya, Mduduzi N. N.; Aaron, Grant J.; Askari, Sufia; Harbour, Catherine; Khondker, Rudaba; Bipul, Moniruzzaman; Sultana, Sabiha; Rahman, Mohammad Ashikur; et al. (Frontiers in Nutrition, 2024)
Background: Anaemia poses a significant public health problem, affecting 1.6 billion people and contributing to the loss of 68.4 million disability-adjusted life years. We assessed the impact of a market-based home fortification program with micronutrient powder (MNP) called Pushtikona-5 implemented by Bangladesh Rural Advancement Committee (BRAC) on the prevalence of anaemia among children aged 6–59 months in Bangladesh. Methods: We used a modified stepped wedged design and conducted three baseline, two midline, and three endline surveys to evaluate the Pushtikona-5 program implemented through three BRAC program platforms. We interviewed children’s caregivers, and collected a finger-prick blood sample from children to measure hemoglobin concentration. We also collected data on coverage of Pushtikona-5 and infant and young child feeding (IYCF) practices. We performed bivariate and multivariable analysis and calculated adjusted risk ratios (ARRs) to assess the effect of program outcomes. Results: A total of 16,936 households were surveyed. The prevalence of anaemia was 46.6% at baseline, dropping to 32.1% at midline and 31.2% at endline. These represented adjusted relative reductions of 34% at midline (RR 0.66, 95%CI 0.62 to 0.71, p-value < 0.001) and 32% at endline (RR 0.68, 95%CI 0.64 to 0.71, p-value < 0.001) relative to baseline. Regarding MNP coverage, at baseline, 43.5% of caregivers surveyed had heard about MNP; 24.3% of children had ever consumed food with MNP, and only 1.8% had consumed three or more sachets in the 7 days preceding the survey. These increased to 63.0%, 36.9% and 4.6% respectively at midline and 90.6%, 68.9% and 11.5% respectively at endline. Conclusion: These results show evidence of a reduction in the prevalence of anaemia and an improvement in coverage. This study provides important evidence of the feasibility and potential for impact of linking market-based MNP distribution with IYCF promotion through community level health workers.